Evaluasi Performa Algoritma Decision Tree C4.5 Pada Dataset Bank Marketing Dengan Telepon Langsung - Hidayatullah, Dikot Syarif; Widhakdo, Rahman Bayu; Arivianto, Ahmad; Taqwim, Muhammad Lutfi; Yusa, Mochammad (Pandawan Incorporation, Alphabet Incubator Universitas Raharja, 2019)
Marketing is an activity to promote, sell and spearhead a company in running a business to get success. In this case marketing includes socialization activities and also advertising from a product to consumers, especially in the case of the Bank that markets time deposit products to customers by calling customers directly. So many ways can be developed to produce an effective marketing outcome. Therefore, the need for an evaluation of direct telephone marketing activities to determine the performance, knowledge and rule in the form of a decision tree from the marketing process. To obtain evaluation results, data mining testing classification is needed by using the Decision Tree C4.5 Algorithm. The Decision Tree C4.5 algorithm can change very large facts into decision trees that represent rules and accurately predict target classes using interrelated variables. So the evaluation results can be used as material for consideration by the bank in evaluating the success rate of marketing techniques by calling customers directly. Keywords: Marketing, Classification, Algorithm Decision Tree C4.5, Bank